AKUNTABILITAS HUKUM CORPORATE GUARANTEE DALAM PERJANJIAN PEMBIAYAAN INVESTASI: KAJIAN TERHADAP DEBITUR WANPRESTASI - Nurhandayani, Pina; Ratnawati, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Ensiklopedia of Journal, 2025)
Abstract: This research aims to analyze the legal accountability of Corporate guarantees in investment financing agreements, especially when the debtor defaults. The Corporate guarantee, as a form of company-backed security, plays an important role in providing protection to creditors against the risk of the debtor’s inability to fulfill obligations. The main issue in this study is how legal protection is provided for the Corporate guarantee and the creditor in bearing risks when the debtor defaults. This research employs a normative approach based on legislation related to Corporate guarantees. Secondary legal sources used in this study include laws and regulations, scholarly journals, books, and other legal products relevant to the issue, along with an analysis of policies and legal rules directly related to the researched matter. This approach aims to provide a strong legal basis for resolving related issues. The research findings indicate that the accountability of Corporate guarantees still requires stricter regulations in cases of debtor default, and legal protections for both creditors and Corporate guarantees should be strengthened by implementing clearer and more stringent rules regarding the execution of company-backed security in the event of debtor default.Keywords: Legal Accountability. Default. Legal Protection